The Cave 3 Copper Scroll: a symbolic journey - Høgenhaven, Jesper (Studies on the texts of the desert of Judah, 2020)
In The Cave 3 Copper Scroll: A Symbolic Journey, Jesper Høgenhavn presents a reading presents of the Copper Scroll as a literary composition, with a deliberately designed structure, composed to cope with turbulent circumstances during the 1st century CE.